Shrinkage Effect of Vacuum Casting Process Parameters using Taguchi Method - Ahmad, Mohd Nazri; Maidin, Nurul Ain; Ab Rahman, Mohd Hidayat; Osman, Mohd Hairizal; Wahid, Mohammad Khalid; Mohd Basir, Mohamad Faris (International Journal of Integrated Engineering, 2019)
This paper investigates the optimization of vacuum casting process by using Taguchi method. Vacuum casting process is a one of the method in Rapid Tooling Technology. The parts produced by vacuum casting process has it accuracy varies with the changes of the process parameters of the machine such as resin temperature, vacuum pressure time, mould temperature and some others. In order to optimize 3 parameters which are resin temperature, mould temperature and vacuum pressure time, the Lâ€™9 orthogonal array was used. From the results, it shows that the optimum parameters that may improve the shrinkage effect are resin temperature (30 Â°C), mould temperature (60 Â°C) and vacuum pressure time (5 min.). The shrinkage values between default and optimum parameter are 0.159mm and 0.336mm respectively. Thus, the improvement on shrinkage effect was 52.4 percent. The study demonstrates that the better dimensional accuracy of vacuum casting process can be optimized using Taguchi Method.